The Derma of Crisis: Imagining Athens in Crisis as an Urban Collage - Ferentinos, Panagiotis (2021)
A close look at the urban surfaces of Athens during the years of the economic crisis reveals the extensive phenomenon of the people’s interaction with the surface of the cityscape, the skin of Athens. A derma of crises that reflects Greece’s socio-political conditions over this period, and the austerity measures enforced by the official state. This rapidly transformed and ever-changing surface imagery can be recorded and used for reading and further understanding of how the public sphere responds to this period of decline, and reacts to the recession’s strategies of sovereignty. The urgency to document, give prominence to this urban field and examine it as a whole is of pivotal importance, considering the fact that the official authorities (such as the mayor of Athens) have recently taken action to eliminate the urban traces. However, these inscriptions bear witness to the continuous crisis mirrored on the Athenian walls and architectural volumes. Over the last years, there have been numerous scholars and researchers that have engaged with the study of the Athenian cityscape. Nonetheless, they particularly focus on graffiti, street art and slogans, and this engagement sometimes facilitates the emerging artistry or the discussion of socio-political connotations. In contrast to this, this article moves towards the identification of the phenomenon as a dynamic potential of a derma–city skin and does not specifically focus on them as mere details (often intentionally made, e.g. a graffiti). It examines the wholeness, the anonymity, the unintentional activity; how they contribute to the formulation of an urban collage, an assemblage of visual elements that co-exist making Athens a unique case of an over-marked city. The study of various dimensions of this skin and of the virtual preservation means aims to add a further layer of understanding to the urban space as a main field of socio-political connotations during the crisis.